Lush pastures, grassy meadows - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 2000)
Pasture management in South Africa. Edited by N M Tainton, University of Natal Press. 2000. 372 pp. ISBN 0 86980 959 8 CTA number 988. 80 Credit points